1999
DOI: 10.1177/002215549904700708
|View full text |Cite
|
Sign up to set email alerts
|

Connexin45, a Major Connexin of the Rabbit Sinoatrial Node, Is Co-expressed with Connexin43 in a Restricted Zone at the Nodal-Crista Terminalis Border

Abstract: The pacemaker of the heart, the sinoatrial (SA) node, is characterized by unique electrical coupling properties. To investigate the contribution of gap junction organization and composition to these properties, the spatial pattern of expression of three gap junctional proteins, connexin45 (Cx45), connexin40 (Cx40), and connexin43 (Cx43), was investigated by immunocytochemistry combined with confocal microscopy. The SA nodal regions of rabbits were dissected and rapidly frozen. Serial cryosections were double l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 32 publications
7
106
0
Order By: Relevance
“…This is in agreement with data obtained from the mouse SAN by Verhijck et al (2001) and Miquerol et al (2004). However, Kwong et al (1998) and Coppen et al (1999) reported that Cx40 protein is widely distributed in the SAN of dogs and rabbits, respectively. Therefore, expression of Cx40 in the SAN may vary among species.…”
Section: Differences In Gene Expression Between San and Atrial Musclesupporting
confidence: 92%
“…This is in agreement with data obtained from the mouse SAN by Verhijck et al (2001) and Miquerol et al (2004). However, Kwong et al (1998) and Coppen et al (1999) reported that Cx40 protein is widely distributed in the SAN of dogs and rabbits, respectively. Therefore, expression of Cx40 in the SAN may vary among species.…”
Section: Differences In Gene Expression Between San and Atrial Musclesupporting
confidence: 92%
“…15,16 There may be a gradient in coupling in the SA node: in the periphery of the SA node, g j may be higher than in the center. 17,18 Figure 3 shows that even in this case (peripheral lattice with high g j and central lattice with low g j ), the mosaic model cannot explain the difference in cycle length between peripheral and central tissue. The mosaic model is based on the assumptions that there are a substantial number of atrial cells in the SA node and that the properties of SA node cells are uniform.…”
Section: Discussionmentioning
confidence: 93%
“…The mosaic model is based on the assumptions that there are a substantial number of atrial cells in the SA node and that the properties of SA node cells are uniform. These assumptions may not be valid, however, because (1) atrial muscle abuts the SA node but is not connected to it, 18 and it is important to remove this atrial muscle when isolating cells, and (2) in the study of Wilders et al, 5 in which no relationship was found between electrical activity and cell size, "single" SA node cells with a capacitance (measure of cell size) Ͼ115 pF are included. Such high values indicate cell clusters and invalidate any conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Expression patterns of all cardiac Cxs are shown in Figure 1. Cx43, the major Cx forming GJ channels between working cardiomyocytes of atria and ventricles, is also expressed in the network of Purkinje fibers forming the distal part of the ventricular conduction system (Beyer et al 1989, Gourdie et al 1993, Coppen et al 1999a). Cx40 colocalizes with Cx43 in the atrial working myocytes and is abundantly expressed in the His bundle, bundle branches, and subendocardial network of Purkinje fibers, that is, structures with high conduction velocities.…”
Section: Expression Of Cxs In the Heart Of Rodentsmentioning
confidence: 99%